Expanding the role of advanced practice providers (APPs) in cancer clinical trials. Issue 28 (1st October 2022) - Williams, Erin Fenske; Macchiaroli, Alyssa; Bazzell, Angela F.; Brucker, Edie; Gerber, David E
Abstract : 60 Background: Advanced Practice Providers (APPs) represent a growing and increasingly important component of the oncology workforce. However, APP roles in clinical research are not clearly understood, and certain policies may limit participation. For instance, National Cancer Institute (NCI) Cancer Therapy Evaluation Program (CTEP) historically prohibited APPs from signing orders on CTEP-sponsored studies, even at centers where APPs have antineoplastic privileges allowing them to order cancer treatments as standard therapy or on non-CTEP studies. At the UT Southwestern Harold C. Simmons Comprehensive Cancer Center (SCCC), more than 100 active CTEP-sponsored trials account for approximately 30% of therapeutic enrollment. Given these considerations, we approached CTEP regarding potential policy change. Methods: In early 2020, we raised the issue of disparities in allowed APP delegation between (1) CTEP trials and (2) standard practice and non-CTEP trials to NCI/CTEP leadership. Later that year, CTEP organized a discussion on the topic with SCCC representatives and other stakeholders. Subsequently, NCI deployed a survey to National Clinical Trials Network (NCTN) and Experimental Therapeutics Clinical Trials Network (ETCTN) centers asking about the role of APPs at their respective institutions. Results: Following the survey, CTEP revised its policy, allowing appropriately credentialed APPs to sign treatment orders on CTEP-sponsored trials, effective September 1, 2021. After completing required regulatory steps to update trial protocols at UTSW SCCC, approved APPs began signing cancer clinical trial treatment orders in January 2022. Since that time, the proportion of trial treatment orders signed by APPs at SCCC has increased from 1% in January 2022 to 20% in May 2022. Conclusions: The role of APPs in cancer care can be further enhanced by alleviating barriers and allowing providers to perform at the full scope of practice, thereby further integrating care teams critical to compliant and safe clinical trial participation.